Guinea-Bissau (2014 - 2016). An empirical study of economic and social human rights in a fragile state. - Proença, Carlos Sangreman (Advances in Social Sciences Research Journal, 2018)
<span style="line-height: 115%; font-family: 'Times New Roman','serif'; font-size: 10pt; mso-fareast-font-family: 'Times New Roman'; mso-ansi-language: EN-US; mso-fareast-language: PT; mso-bidi-language: AR-SA;" lang="EN-US">The purpose of this article is to analyze the situation of the economic and social human rights in Guinea-Bissau. It uses data collected from seven of the eight administrative regions of the country between 2014 and 2016, for a project called "Observatory of Rights" in the fields of education, health, justice, housing, sanitation and livelihood from schools, health centers, jails and police stations and families. <span style="color: #222222; line-height: 115%; font-family: 'Times New Roman','serif'; font-size: 10pt; mso-fareast-font-family: Calibri; mso-ansi-language: PT; mso-fareast-language: PT; mso-bidi-language: AR-SA;">With 5 prime ministers since the elections of 2014, the political instability installed in the country shapes the life of citizens in all aspects and does not allow a positive evolution of economic and social human rights in the country.<span style="line-height: 115%; font-family: 'Times New Roman','serif'; font-size: 10pt; mso-fareast-font-family: 'Times New Roman'; mso-ansi-language: EN-US; mso-fareast-language: PT; mso-bidi-language: AR-SA;" lang="EN-US">This article frames the analysis of the data into an interpretation of the situation of that period and elaborates the conclusions in the form of scenarios for the short-term future, <span style="color: #222222; line-height: 115%; font-family: 'Times New Roman','serif'; font-size: 10pt; mso-fareast-font-family: Calibri; mso-ansi-language: PT; mso-fareast-language: PT; mso-bidi-language: AR-SA;">including the possibility that the military might decide to take power as they have done in the recent past (2012)<span style="line-height: 115%; font-family: 'Times New Roman','serif'; font-size: 10pt; mso-fareast-font-family: 'Times New Roman'; mso-ansi-language: EN-US; mso-fareast-language: PT; mso-bidi-language: AR-SA;" lang="EN-US">.